2017
DOI: 10.1136/bmjopen-2016-015758
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stroke and associated risk factors: a population based cross sectional study from northeast China

Abstract: ObjectivesEpidemiological studies aimed at stroke and its risk factors can help identify persons at higher risk and therefore promote stroke prevention strategies. We aimed to explore the current prevalence of stroke and its associated risk factors in northeast China.DesignPopulation based cross sectional study.SettingData were collected using a structured precoded questionnaire designed by the Stroke Screening and Prevention Programme of the National Health and Family Planning Commission of China, between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
64
2
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 46 publications
(39 reference statements)
13
64
2
7
Order By: Relevance
“…The finding of this study revealed that ischemic type of stroke was predominated in 80.1% of total stroke victims. This is in line with various studies conducted at different part of world; 55.6% (8), 56.7% (9), 65.8% (10), 69.4% (14), 85.7% (12) and 91.7% (18). Contrastingly, hemorrhagic stroke was the most common in studies conducted at St. Paul's Teaching Hospital (61.3%) (13), Jimma (64.3%) (19) and Rwanda (65%) (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of this study revealed that ischemic type of stroke was predominated in 80.1% of total stroke victims. This is in line with various studies conducted at different part of world; 55.6% (8), 56.7% (9), 65.8% (10), 69.4% (14), 85.7% (12) and 91.7% (18). Contrastingly, hemorrhagic stroke was the most common in studies conducted at St. Paul's Teaching Hospital (61.3%) (13), Jimma (64.3%) (19) and Rwanda (65%) (20).…”
Section: Discussionsupporting
confidence: 92%
“…This may be probably due to small sample size in our study. It is in accordance with other hospital based study done at University of Gondar Teaching Hospital (8) and population based cross sectional study in China (18). In contrast to this, a study done in Rwanda showed that initial presentation with severe stroke was the major cause of death among stroke patients (20).…”
Section: Discussionsupporting
confidence: 89%
“…These findings were consistent with those of previous studies on stroke prevalence in China [1,20]. The prevalence of stroke in Sichuan was higher than the nationwide findings [1,6], but was lower than in northeast China [20]. The prevalence of stroke increased with age, and this was consistent with other studies [25].…”
Section: Discussionsupporting
confidence: 92%
“…We have also identified a high prevalence of stroke and stoke related risk factors among adults aged ≥40 years, and found that age, male, diabetes, hypertension, dyslipidemia, lack of exercise, overweight were associated with a high prevalence of stroke and ischemic stroke. These findings were consistent with those of previous studies on stroke prevalence in China [1,20]. The prevalence of stroke in Sichuan was higher than the nationwide findings [1,6], but was lower than in northeast China [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation